Molecular signaling and mechanisms of low-level laser-induced gene expression in cells involved in orthodontic tooth movement - Nutthakarn Ratanasereeprasert; Li-Fang Hsu; Shih-Kai Wang; Yi-Jane Chen; Jui-Heng Chang; Chung-Chen Jane Yao (Journal of the Formosan Medical Association, 2024)
Background: The study aimed to observe molecular signaling, including reactive oxygen species (ROS) and mitochondrial membrane potential (ΔΨm), to evaluate the alteration of gene expression by low-level laser therapy (LLLT) and the correlation between its mechanisms and the NF-kB pathway in cells involved in orthodontic tooth movement. Methods: Osteoblast-like cells (MG63), immortalized periodontal ligament cells (iPDL), and M1 macrophage-like cells were irradiated by 980-nm LLLT with energy densities of 1 and 10 J/cm2 ΔΨm and intracellular ROS were monitored using fluorescent probes. The changes of mRNA expression were assessed using reverse transcription polymerase chain reaction (RT-PCR). NF-kB inhibitor, ROS scavenger, and ΔΨm suppressor were used to analyze signals associated with the regulation of gene expression. Finally, Western blot analysis was performed to confirm NF-kB signaling after LLLT. Results: We found the increases of ΔΨm and ROS in all three cell types after LLLT, but no significant difference was observed between 1 and 10 J/cm2 LLLT. Regarding gene expression, some target genes were upregulated in MG63 6 h, 12 h, and 1 day after LLLT and in iPDL cells 12 h and 1 day after LLLT. However, no changes occurred in M1 cells. The inhibitor that significantly reduced most changes in gene expression was NF-kB inhibitor. Western blot analysis showed the increase in p-IkBα level after LLLT in iPDL and MG63, but not in M1. Conclusion: The 980-nm LLLT increased ΔΨm and ROS production in all three cell types. However, changes in gene regulation were found only in MG63 and iPDL cells, which related to the NF-kB pathway.